PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION (LSQ) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 6 PARIAMAN - Eka Putri, Desfri Yeni; Rahmi, Rahmi; k, Desi (Pendidikan Matematika, 2014)
ABSTRAKThe background from this research is a low comprehension studentsâ mathematics concept in class VIII of SMPN 6 Pariaman. The aim from this research is to know the comprehension studentsâ mathematics which use Learning Starts with A Question (LSQ) more better from a comprehension studentsâ with use a conventional learning. A kind from this research is experiment with random design to subject. The instrument is study comprehension mathematics concept test like essay with reliability test is Â = 0,83. Analysis data technique which use is t-test in one side with MINITAB. According to the hypothesis, the result P-value = 0,011 more smaller from Î± = 0,05, so that the hypothesis research is accepted. The conclusion from this research is a comprehension studentsâ mathematics with use Learning Starts with A Question (LSQ) more better from with use conventional learning.